EFEKTIVITAS PENGGUNAAN BAHAN AJAR AUDIO BERBENTUK VIDEO TERHADAP MOTIVASI BELAJAR SISWA - Muslem, Anna Fadhla (Postgraduate Program UIN Sultanah Nahrasiyah Lhokseumawe, 2025)
The aim of this research is to examine the effectiveness audio-visual teaching materials in the form of videos to enhance students' motivation in grade IV at SDIT Khairul Ummah. The research employs a descriptive qualitative approach involving 30 students and Teachers as research subjects. Data were collected through unstructured interviews, participatory observation, and document collection. The data were then analyzed through transcription, coding, grouping into main themes, and in-depth interpretation based on the ARCS theory (Attention, Relevance, Confidence, Satisfaction). The findings indicate that the video media effectively captures students' attention, relates to their real-life experiences, boosts their confidence, and provides a satisfying learning experience. The use of audio-visual teaching materials has been proven to significantly motivate students and reduce boredom during conventional learning processes. These results highlight the importance of integrating videos into learning activities to increase students' interest and motivation, making the learning process more enjoyable and meaningful.